Epidemiological characteristics of hepatitis B and C in patients with inflammatory arthritis: Implications from treasure database - Ersozlu, Emine Duygu; Ekici, Mustafa; Coskun, Belkis Nihan; Badak, Suade Ozlem; Bilgin, Emre; Kalyoncu, Umut; Ertenli, Ihsan (Turkish League Against Rheumatism, 2023)
Objectives: This study aimed to evaluate the hepatitis B (HBV) and C (HCV) frequency and clinical characteristics among patients with rheumatoid arthritis (RA) or spondyloarthritis (SpA) who receive biological treatments.Patients and methods: The observational study was conducted with patients from the TReasure database, a web-based prospective observational registry collecting data from 17 centers across Turkiye, between December 2017 and June 2021. From this database, 3,147 RA patients (2,502 males, 645 females; median age 56 years; range, 44 to 64 years) and 6,071 SpA patients (2,709 males, 3,362 females; median age 43 years; range, 36 to 52 years) were analyzed in terms of viral hepatitis, patient characteristics, and treatments used.Results: The screening rate for HBV was 97% in RA and 94.2% in SpA patients. Hepatitis B surface antigen (HBsAg) positivity rates were 2.6% and 2%, hepatitis B surface antibody positivity rates were 32.3% and 34%, hepatitis B core antibody positivity rates were 20.3% and 12.5%, HBV DNA (deoxyribonucleic acid) positivity rates were 3.5% and 12.5%, and antibody against HCV positivity rates were 0.8% and 0.3% in RA and SpA patients, respectively. The HBsAg-positive patients were older and had more comorbidities, including hypertension, diabetes, and coronary artery disease. In addition, rheumatoid factor (RF) positivity was more common in HBsAg-positive cases. The most frequently prescribed biologic disease-modifying antirheumatic drugs were adalimumab (28.5%), etanercept (27%), tofacitinib (23.4%), and tocilizumab (21.5%) in the RA group and adalimumab (48.1%), etanercept (31.4%), infliximab (22.6%), and certolizumab (21.1%) in the SpA group. Hepatitis B reactivation was observed in one RA patient during treatment, who received rituximab and prophylaxis with tenofovir.Conclusion: The epidemiological characteristics of patients with rheumatic diseases and viral hepatitis are essential for effective patient management. This study provided the most recent epidemiological characteristics from the prospective TReasure database, one of the comprehensive registries in rheumatology practice.
Keywords: HBV; HCV; rheumatic diseases; rheumatoid arthritis; spondyloarthritis; TReasure; viral hepatitis; viral reactivation